Interactive effects of salinity and dietary lipid sources on growth, hepatic lipid metabolism, and transcriptomic profiles in spotted sea bass (Lateolabrax maculatus) - Jin, Guoxiong; Zhang, Lu; Ai, Qinghui; Mai, Kangsen; Chen, Xiaoru (Frontiers in Physiology, 2025)
This study investigated the interactive effects of salinity and dietary lipid sources on growth performance, hepatic lipid metabolism, and the underlying molecular mechanisms in spotted sea bass (Lateolabrax maculatus). Fish were reared at 0‰ or 20‰ salinities and fed diets containing either fish oil (FO) or soybean oil (SO) for 126 days. Results demonstrated that rearing fish at 20‰ salinity significantly enhanced growth performance but concurrently increased hepatic lipid accumulation compared to rearing at 0‰ salinity. Under the same salinity conditions, dietary lipid sources had no significant effect on fish growth performance, however, compared to FO-based diet the SO-based diet significantly increased hepatic lipid accumulation. Salinity significantly enhanced the growth-promoting effect of SO-based diet, but also aggravated hepatic lipid accumulation in fish. The combination of salinity and FO significantly inhibited lipid synthesis (FAS and ACC activities) and lipolysis (ATGL, MGL activities). RNA-seq identified 9,854 common differentially expressed genes (DEGs). GO enrichment analysis revealed that salinity primarily altered processes related to membrane integrity and energy metabolism, whereas lipid sources regulated organelle structure and fatty acid synthesis. Their interaction regulated catalytic activity and membrane integration processes. KEGG pathway analysis identified salinity-driven shifts in energy/carbohydrate metabolism and lipid-energy sensing, whereas lipid sources dominated fatty acid synthesis. GSEA further highlighted lipid source-dependent regulation of glycerolipid metabolism and unsaturated fatty acid synthesis, alongside salinity-responsive pathways including Ppar signaling and steroid biosynthesis. Key lipid-related genes (pltp, dgat1, cyp24a1, acadsb) exhibited differential expression patterns modulated by salinity-lipid interactions. These results support the development of precise nutritional strategies for raising spotted sea bass in varying salinity environments. Replacing FO with SO across salinities is viable when combined with functional additives to regulate lipid metabolism; however, SO inclusion rates should be adjusted downward in seawater to minimize lipid accumulation and optimize performance.